Bendamustine treatment of haematological malignancies: significant risks of opportunistic viral, fungal and bacterial infections - Tony K.Y. Wu; Karen H.K. Tang; Yu-Yan Hwang; Thomas S.Y. Chan; Eric Tse; Yok-Lam Kwong (Hematology, 2022)
Objectives Bendamustine is a standard treatment for low-grade B-cell lymphomas, and considered safe in clinical trials. Its safety in routine practice might be different.Methods We retrospectively analyzed the infection complications in an unselected cohort of patients treated with bendamustine over a nine-year period. Patients were regularly monitored for blood counts and cytomegalovirus (CMV) reactivation by antigen assay and polymerase chain reaction. They received granulocyte colony stimulating factor for neutropenia, and routine anti-pneumocystis and optional anti-fungal prophylaxis.Results There were 179 men and 127 women at a median age of 61.5 (20–90) years, 52% receiving bendamustine for relapsed/refractory disease. Malignancies included low-grade B-cell lymphomas (54%), myeloma (10%), T-cell lymphomas (11%), Hodgkin lymphoma (2%) and other lymphoid neoplasms (23%). Most patients had good performance status (Eastern Cooperative Oncology Group score: 0–1, 72%). CMV reactivation occurred in 58 patients (19%) at a median age of 68 (39–85) years. Univariate analysis showed CMV reactivation to be significantly associated with elevated lactate dehydrogenase (P = 0.045), decreased albumin (P = 0.003) and older age (reactivation versus no reactivation: 66.3 ± 11.4 versus 59.4 ± 14.5 years, P = 0.0016). Age remained the only significant risk on multivariate analysis. CMV reactivation resulted in retinitis (N = 4), ependymitis/ventriculitis (N = 1) and duodenitis/colitis (N = 1). Invasive fungal disease occurred in five patients (candidemia, N = 2; aspergillosis N = 1; cryptococcemia, N = 1; scedosporiosis, N–1). Nineteen patients had culture positive septicaemia.Conclusion Our observations showed that even with a vigorous anti-infective strategy, bendamustine treatment was still associated with significant risks of bacterial and opportunistic viral and fungal infections.